Embedded systems architecture : a comprehensive guide for engineers and programmers - Noergaard, Tammy (Newnes, 2013)
"This book fills a void. Most books address only portions of the embedded problem. As the title indicates, this one is uniquely comprehensive. I consider it a must-read"--Review of the 1st Edition. Jack Ganssle, embedded author, lecturer, consultant. Embedded Systems Architecture is a practical and technical guide to understanding the components that make up an embedded system's architecture. This book is perfect for those starting out as technical professionals such as engineers, programmers and designers of embedded systems; and also for students of computer science, computer engineering and electrical engineering. It gives a much-needed 'big picture' for recently graduated engineers grappling with understanding the design of real-world systems for the first time, and provides professionals with a systems-level picture of the key elements that can go into an embedded design, providing a firm foundation on which to build their skills. A true introductory book, provides a comprehensive get up and running reference for those new to the field, and updating skills: assumes no prior knowledge beyond undergrad level electrical engineering. Addresses the needs of practicing engineers, enabling it to get to the point more directly, and cover more ground. Covers hardware, software and middleware in a single volume. Includes a library of design examples and design tools, plus a complete set of source code and embedded systems design tutorial materials from companion website
Keywords: Embedded computer systems -- Design and construction.; elektronické knihy; electronic books